Polimorfismos genéticos associados à ocorrência e gravidade da síndrome congênita do Zika vírus - Santos, Camilla Natália Oliveira (2019)
Zika virus (ZIKV) infection varies from asymptomatic to severe and can lead to severe neurological disorders, such as microcephaly. The immune response (IR) developed during ZIKV infection has not been fully elucidated and there are difficulties in knowing if the IR products detected during or after infection act as a cause or consequence of the infection. Moreover, the determining factors for the most severe forms associated with the infection are still unclear. ZIKV infection, like other infectious diseases, is multifactorial, in which susceptibility or resistance and clinical pattern are influenced by environmental and genetic factors of the host, with multigenic inheritance. Genetic determinants such as single nucleotide polymorphisms (SNPs), which are sites in the genome where variants of a nucleotide are common in the population, can act by modulating IR and contributing to the course of the different clinical outcomes. The present study evaluated the association of SNPs in CD209, TNFα, CXCL8, IL-4, IL-6, CCL2, TLR3, TLR4 and MICB genes with ZIKV infection by a case-control study. The case group was composed of children with microcephaly associated with ZIKV infection and the control group, composed of healthy children who were born in the same period of the ZIKV outbreak. In addition, we also compared the parents of the children with microcephaly with control mothers who had healthy children in the same period of the ZIKV outbreak, living in an endemic area to ZIKV infection. Genomic DNA from patients and controls were obtained and used in the genotyping of functional SNPs in candidate genes and the association with ZIKV infection was verified using the Chi-square test or Fisher's Exact Test. In this study, an association was found between the T allele in the SNP rs3775291 in the TLR3 gene with the occurrence of microcephaly resulting from Congenital Syndrome of ZIKV (SCZ). This allele was more frequent in the case mothers when compared to the control mothers. Moreover, we observed association of SNP rs1799964 in the TNFα gene in the newborns with severe microcephaly, in which the T allele was more frequent in children with severe microcephaly than in children with mild microcephaly at birth. In conclusion, this work brings together for the first time an association between the variant associated with a possible deleterious effect on the protein structure of TLR3, that may impair TLR3 signaling pathways in mothers who had children with microcephaly, suggesting that the impairment of this inflammatory pathway is an important factor in the control of ZIKV infection in the mothers and induction of neurological lesions in the fetus brain. In addition, the T variant of TNFα SNP, associated with low production of this cytokine, was more frequent in children with more severe microcephaly at birth, and it is possible that the lower TNF production reduces antiviral defense in the fetus, and contributes to central nervous system invasion by ZIKV. These data provide support for a better understanding of the immunological mechanisms, influenced by genetic factors, which predispose to different outcomes during ZIKV infections.